Environmental pollutants affecting children's growth and development: Collective results from the MOCEH study, a multi-centric prospective birth cohort in Korea. (April 2020) - Shah, Surabhi; Jeong, Kyoung Sook; Park, Hyesook; Hong, Yun-Chul; Kim, Yangho; Kim, Byungmi; Chang, Namsoo; Kim, Suejin; Kim, Yeni; Kim, Bung-Nyun; Kwon, Hojang; Bae, Sanghyuk; et al.
Highlights: The MOCEH study contributes to the challenges in children's environmental health. Exposure to environmental pollutants influenced children's growth and development. Critical period of exposure to pollutants affecting children's health was identified. Abstract: Background: The Mothers and Children's Environmental Health study (MOCEH) is a multi-centric prospective birth cohort study investigating effects of various environmental pollutants like heavy metals, endocrine disruptors, air pollutants, nutrition and lifestyle on birth outcomes, growth and development, health and disease of children. In this study, we report all the outcomes from the MOCEH study describing the different environmental pollutants affecting children's health and disease. Methods: In MOCEH study, 1, 751 pregnant women in their first trimester were recruited at 3 centers from 2006 to 2010 in South Korea. The children were followed from birth up to 6 years. Information on health outcomes of children including birth parameters, demographic characteristics, medical and child-rearing history, and nutritional status, were repeatedly obtained through the follow-ups by questionnaires administration, clinical evaluation, and biological specimen collection and measurements. Prenatal and postnatal measurement in biospecimen, i.e., lead, mercury, cadmium, manganese, 1-hydroxypyrene, 2-naphthol, malonadialdehyde, hippuric acid, bisphenol A and phthalate metabolites, and measurement in air samples, i.e., particulate matter, nitrogen dioxide, and total volatile organic compounds were performed. Results: The results show the adverse effect of prenatal exposure to heavy metals like mercury, lead and cadmium on children's physical, cognitive and neurobehavioral development. Exposure to endocrine disruptors, air pollution, second hand smoke, and mother's lifestyle during pregnancy affects children's growth and development. We also identified specific window periods of exposure of pollutants significantly related to children's health outcomes. Conclusion: The collective results from MOCEH study provide strong scientific evidence that exposures to prenatal and postnatal environmental pollutants have a negative effect on growth and development of children, which will be useful in implementing effective national policy to improve children's environmental health.